2019
DOI: 10.15361/1984-5529.2019v47n4p411-418
|View full text |Cite
|
Sign up to set email alerts
|

Propriedades físicas do solo e produtividade de mandioca em diferentes manejos de coberturas do solo

Abstract: Plants used as green manure can be managed in different ways. Thus, this study evaluates the impact of managing Crotalaria ochroleuca and weeds on cassava yield, soil physical properties and weed management. The treatments consisted of cassava cultivation on four soil cover types: 1-mowed and incorporated C. ochroleuca; 2-mowed C. ochroleuca; 3-mowed and incorporated weed community; and 4-weeded control. The incorporation of C. ochroleuca and weeds reduced soil density and increased total soil porosity compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Thus, the use of cover crops is an alternative for suppressing weeds, reducing the demand for herbicides and the risks of food contamination (Ghahremani et al, 2021;Mennan et al, 2020;Proctor, 2021). Moreover, cover crops as legumes and grasses can improve the physical properties of soil in different forms and several studies have shown these benefits (Demir and Işõk, 2020;R os and Hirata, 2019;Soares et al, 2021). Although cassava is known worldwide for its rusticity and low nutritional requirements, physical properties of soil, such as bulk density and porosity, can be crucial for this crop, since these properties are directly related with the resistance of penetration and expansion of roots in the soil.…”
mentioning
confidence: 99%
“…Thus, the use of cover crops is an alternative for suppressing weeds, reducing the demand for herbicides and the risks of food contamination (Ghahremani et al, 2021;Mennan et al, 2020;Proctor, 2021). Moreover, cover crops as legumes and grasses can improve the physical properties of soil in different forms and several studies have shown these benefits (Demir and Işõk, 2020;R os and Hirata, 2019;Soares et al, 2021). Although cassava is known worldwide for its rusticity and low nutritional requirements, physical properties of soil, such as bulk density and porosity, can be crucial for this crop, since these properties are directly related with the resistance of penetration and expansion of roots in the soil.…”
mentioning
confidence: 99%